Fekunditas Udang Galah (Macrobrachium rosenbergii ) Betina Pasca Ablasi Unilateral dan Suplementasi Vitamin E pada Pakan - Rachmawati Nasution; Moh. Husein Sastranegara; Yulia Sistina (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
This study reports on giant freshwater prawn fecundity with or without unilateral ablation treatment combined with alpha tocopherol (vit E) during 3 month culture. This exsperimental study applied 8 combination treatments of 4 different vit E dosages, i.e. 0, 200, 400, and 600 IU per kg feed with or without unilateral ablation. The results showed that treatments very highly significantly different (p<0,01) in fecundity with the 200 IU vit E dose combined with unilateral ablation was the best (45.228 ± 3.867 egg) optimum resulted in fecundity of the treated females. The overall fecundities averages were ablation group with 0 IU = 41.835 ± 837 eggs; 200 IU = 45.228 ± 3.867 eggs; 400 IU = 43394 ± 1523 eggs ; and the 600 IU = 43.718 ± 2.255 eggs, and for the non ablation with vit E group were 0 IU = 45.293 ± 2.899 eggs, 200 IU = 44.106 ± 1.759 eggs, 400 IU = 46.623 ± 2.556 eggs, and 600 IU=51.824 ± 1.132 eggs. The analysis results also proven that ablation factor gave very highly significantly (p<0,01) and vit E factor separately and in combination with ablation significantly (p<0,05) determined the females fecundity. In conclution, combination of unilateral ablation and tocopherol effective improved fecundity and the combination of unilateral ablation and vit E 200 IU the optimum resulted in giant freshwater prawn females fecundity.